1994
DOI: 10.1139/v94-165
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, spectroscopic, and structural studies of dimethyltellurium(IV) alkylene and diphenyl dithiophosphates. Crystal structures of and

Abstract: and -CH2CEt2CH2-, have been synthesized in 80-90% yields by reaction of the corresponding sodium or ammonium salts of the appropriate dithiophosphoric acids with dimethyltellurium dichloride in toluene. Me,Te[S,P(OPh),], was also prepared in a similar fashion. The compounds have been characterised by elemental analyses -and 'H, l3C, 3 '~, and ' 2 5~e NMR, infrared and Raman spectroscopy. = 0.0295. The immediate environment about tellurium in both molecules is that of the saw-horse structure typical of telluriu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
18
1

Year Published

1995
1995
2015
2015

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 27 publications
(29 citation statements)
references
References 30 publications
10
18
1
Order By: Relevance
“…In other words, the shifts are consistent with the structures in solution apparently remaining the same as the solid state structures of 1-3, where the ligand is monodentate or weakly anisobidentate because the second sulfur atom is oriented toward rather than away from germanium but at a sufficiently large distance to imply, at best, a weak interaction. The shifts are smaller than those-observed for the methyl germanium analogues and considerably smaller than those observed for analogous dimethyltellurium derivatives where AP ranged from 11 to 16 ppm downfield (17). Although the dithiophosphate groups had trast, in the tin and tellurium analogues, the dithiophosphate groups undergo exchange in solution to bring about equivalence for all atoms in the groups, presumably by interchanging the bonded and aniso-bonded sulfur positions, which is consistent with the general tendency for dithio ligands to be bidentate when attached to tin and tellurium (34,35).…”
Section: Compoundcontrasting
confidence: 59%
See 3 more Smart Citations
“…In other words, the shifts are consistent with the structures in solution apparently remaining the same as the solid state structures of 1-3, where the ligand is monodentate or weakly anisobidentate because the second sulfur atom is oriented toward rather than away from germanium but at a sufficiently large distance to imply, at best, a weak interaction. The shifts are smaller than those-observed for the methyl germanium analogues and considerably smaller than those observed for analogous dimethyltellurium derivatives where AP ranged from 11 to 16 ppm downfield (17). Although the dithiophosphate groups had trast, in the tin and tellurium analogues, the dithiophosphate groups undergo exchange in solution to bring about equivalence for all atoms in the groups, presumably by interchanging the bonded and aniso-bonded sulfur positions, which is consistent with the general tendency for dithio ligands to be bidentate when attached to tin and tellurium (34,35).…”
Section: Compoundcontrasting
confidence: 59%
“…This structure is also typical of xanthate derivatives of germanium (3)(4)(5). Recently, we reported the synthesis and characterization of a number of cyclic dithiophosphate derivatives of methylgermanes (6) whose NMR spectra showed unusual features that suggested that the solid state structures were maintained in solution, in contrast to what had been observed in general (7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17) and for tin and tellurium analogues in particular (14,17). Unfortunately, we were only successful in obtaining a crystal structure for one derivative, ~OCH,CE~,CH,$]-C~H~, 3, but have not been able to get data of sufficient quality to fully solve the structures of any of the diphenylgermanium analogues, 6 6 .…”
Section: Introductionmentioning
confidence: 77%
See 2 more Smart Citations
“…There have been a number of reports on the reactions of organotellurium(1V) compounds with a variety of 1,l -dithio ligands, such as O-alkyl dithiocarbonates (1)(2)(3)(4)(5)(6), N,N-dialkyl dithiocarbamates (5)(6)(7)(8)(9)(10)(11)(12)(13)(14), and 0,O-dialkyl(alky1ene) dithiophosphates (4-6, [14][15][16][17][18][19][20][21], as well as a recent extensive review of supramolecular associations in tellurium complexes with sulfur ligands (22). In general, the chemistry of monothio ligands has received much less attention but a few reports have appeared relating to main group element derivatives including those on monothiocarbamate compounds of thallium (23), tin (24,25), and, most recently, tellurium (26) as well as on monothiophosphate compounds of tin (27,28).…”
Section: Introductionmentioning
confidence: 99%